2019
DOI: 10.1042/bsr20190225
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative and endoplasmic reticulum stresses are involved in palmitic acid-induced H9c2 cell apoptosis

Abstract: Palmitic acid (PA) is the most common saturated long-chain fatty acid that causes damage to heart muscle cells. However, the molecular mechanism of PA toxicity in myocardial cells is not fully understood. In the present study, we explored the effects of PA on proliferation and apoptosis of H9c2 cardiomyocytes, and uncovered the signaling pathways involved in PA toxicity. Our study revealed induction of both oxidative and endoplasmic reticulum (ER) stresses and exacerbation of apoptosis in PA-treated H9c2 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 24 publications
6
36
0
Order By: Relevance
“…Under these conditions, ER load is ameliorated by following three methods: (1) a reduction in the entry of newly synthesized proteins into the ER through attenuating protein translation; (2) an increase in the protein-folding capacity by up-regulating ER gene expression; (3) the degradation of misfolded and unfolded proteins through ER-associated degradation (ERAD) and lysosome-mediated autophagy [18, 22, 23]. ER stress occurs widely in several physiological and pathological processes, including development, cell apoptosis, autophagy, and metabolic diseases [18, 24]. The role of ER stress in immune response [25, 26], inflammation [25], and female reproduction [27,28,29,30,31] have also been reported previously.…”
mentioning
confidence: 99%
“…Under these conditions, ER load is ameliorated by following three methods: (1) a reduction in the entry of newly synthesized proteins into the ER through attenuating protein translation; (2) an increase in the protein-folding capacity by up-regulating ER gene expression; (3) the degradation of misfolded and unfolded proteins through ER-associated degradation (ERAD) and lysosome-mediated autophagy [18, 22, 23]. ER stress occurs widely in several physiological and pathological processes, including development, cell apoptosis, autophagy, and metabolic diseases [18, 24]. The role of ER stress in immune response [25, 26], inflammation [25], and female reproduction [27,28,29,30,31] have also been reported previously.…”
mentioning
confidence: 99%
“…Similar to PERK, excessive ERS can lead to the autophosphorylation of IRE1, which then initiate the downstream ASK1-JNK pathway by its phosphokinase activity. As apoptotic factors, the continued expression of JNK and CHOP can cause body injury by blocking the cell cycle and inducing apoptosis [ 26 29 ]. In the present study, after treated with 100 μ M DEX for 24 h, the results showed that the treatment of high-concentration GC leaded to the increased expression of ERS-related proteins GRP78, ATF4, CHOP, ASK1, and JNK in PC12 cells and increased phosphorylation levels of PERK and IRE1.…”
Section: Discussionmentioning
confidence: 99%
“…This subsequently promotes mitochondrial ca 2+ overload, which triggers cell apoptosis by opening the mitochondrial permeability transition pore (43). Oxidative stress promotes ERS, and persistent ERS has been observed to promote mitochondrial dysfunction, which in turn induces oxidative stress (44). As previously mentioned, ERO1α is strongly associated with the generation of ROS, and it has been demonstrated that due to excessive oxidation, ERO1α enhances inositol triphosphate receptor (IP3R) activity, and promotes IP3R-mediated Ca 2+ release and transfer to the mitochondria, facilitating apoptosis (45,46).…”
Section: Discussionmentioning
confidence: 99%